Flow kinematics of focused wave groups on a plane beach in the UK Coastal Research Facility - Borthwick, A; Hunt, A; Feng, T; Taylor, P; Stansby, P (2006)
Measurements are presented of the water particle kinematics of focused wave groups generated in the U.K. Coastal Research Facility. Single and repeated wave groups are considered at normal and 20° incidence to a 1:20 plane beach. The single focused wave groups model extreme transient events without the complication of reflections during the data acquisition process. A symmetry-based separation of harmonics method is used to interpret the water particle kinematics at the point of focus. Although the largest component is linear, there are also considerable second order kinematics terms (both low frequency and high frequency). Away from the free surface, the 2nd order difference contribution to the kinematics is a return current opposed to the direction of wave advance. For repeated wave groups, the measured kinematics confirms the presence of a low frequency free wave, followed by higher frequency waves of the main group and trailing higher order harmonic waves. In the breaker and surf zones, there is also evidence of the saw-tooth behaviour of broken waves, followed by scatter due to breaker-induced turbulence. Pulsatile wave breaking of repeated wave groups at oblique incidence is found to drive a longshore current. © 2006 Elsevier B.V. All rights reserved.